Extraction and purification of cytotoxic compounds from Premna serratifolia L. (Bebuas) for human breast cancer treatment - Salih, Ghassan Ali; Ahmad Raus, Raha; Shaban, Mustaffa Nameer; Abdullah, Norhayati (Kulliyah of Engineering, International Islamic University Malaysia, 2016)
Breast cancer is considered one of the most common cancers all over the world. A huge effort has been spent to create a safe and a cost effective breast cancer treatment. All of these features exist in the plants sources. In this study, the effect of local plant, Premna serratifolia (Bebuas) against MCF-7 cells (human breast adenocarcinoma) was determined. The optimum condition to extract breast cancer cytotoxic compound from the plant was investigated and the exact cytotoxic compound was identified as well. To determine the plant cytotoxicity effect against MCF-7 cells, MTT assay was used. Two important parameters in sonication extraction method which are duration of time and temperature were optimized by carrying out a series of experiments which were designed by Face Centered Central Composite Design (FCCCD). The extraction efficiency of each experiment was determined by measuring the yield of extract and the half maximal inhibitory concentration (IC50) of the extract against MCF-7 cells. The results obtained from the experiments were fitted to second order polynomial model to generate equation that was used to determine best extraction processing condition. Based on the generated equation, the best sonication processing condition to extract the cytotoxic compound is at 30°C and 67 min. Analysis of variance (ANOVA) showed that duration of time has great influence (p<0.05) on the yield of crude extract, while both parameters, time and temperature significantly (p<0.05) affected the IC50 value of the plant extract. Two purified compounds from the plant, acacetin and acacetin-7-O-glycoside were identified responsible for the cytotoxicity activity. Conclusively, in terms of pharmaceutical and medical field applications; the optimal extraction processing condition obtained from this study ensures that the extraction of cytotoxic compound from the plant is conducted at low temperature and short duration of time. Further study on the identified compounds is required as it is a potential candidate for anticancer drug.